Partisipasi Mahasiswa UPGRIS dalam Pilpres 2024 - Farha, Shina Wihda Aulia; Pratiwi, Abela Eka; Prasasti, Febrina Eska; Maulita, Sherly Arvia; Aina, Naila Nur (Pena Edukasia, 2024)
The aim of this research is to determine the form of participation of students, especially UPGRIS students, in the presidential election which will take place on February 14 2024. Presidential elections take place every 5 years in Indonesia. All Indonesian people who are 17 years old are required to participate and vote in the election event. This research approach uses a survey research method which is a type of quantitative research method. Data collection in this research method is carried out by distributing questionnaires. The research results show that students will exercise their right to vote in the upcoming 2024 presidential election, whether they are old voters or new voters. Regarding the age limit for presidential and vice presidential candidates, it was initially determined that the minimum age limit for presidential and vice presidential candidates was 40 years. As is known, the Constitutional Court has held a hearing to pronounce its decision on the judicial review of Article 169 letter q of Law Number 2017 concerning Elections regarding the minimum age limit for presidential candidates (capres) and vice presidential candidates (cawapres) in the plenary court room, MK Building, Jakarta, Monday (16 /10/2023). The article being sued regulates the minimum age limit for presidential and vice presidential candidates, namely 40 years and does not regulate the maximum age limit for presidential and vice presidential candidates. After the case sued by PSI, the Garuda Party and three regional heads, the Constitutional Court tried case Number 90/PUU-XXI/2023 which was filed by a student named Almas Tsaqibbirru Re A. He chose Arif Sahudi, Utomo Kurniawan, et al as legal representatives. The Constitutional Court received this application on August 3 2023. The Petitioner wants the Constitutional Court to change the minimum age limit for presidential and vice presidential candidates to 40 years or experience as a Regional Head at both the Provincial and Regency/City levels. The Constitutional Court also decided to partially grant the applicant's request. This Constitutional Court's decision opens up the opportunity for the Mayor of Solo, Gibran Rakabuming Raka, to compete in the 2024 presidential election. Apart from that, students apparently want a president and vice president with honest, fair character, who have a high leadership spirit, able to bring good change for Indonesia towards A more advanced Indonesia, able to keep its promises, wise and responsible.